A Field Survey on Anthelmintic Resistance in Equine Small Strongyles in Norway - Ihler, C. E. (Acta Vet Scand, 1995)
A field survey at 17 stables involving 221 horses was performed to evaluate the presence of anthelmintic resistance in the equine small strongyles (cyathostomes). The horses were allocated into treatment groups, and resistance to fenbendazole (FBZ), pyrantel pamoate (PYR) and ivermectin (IVM) was tested by the faecal egg count reduction test (FECR-test). Faecal samples were collected at the time of treatment, 14 days post treatment and 90 days post treatment. Resistance to FBZ, which was defined as a faecal egg count reduction <95%, was found in 14 out of 17 stables. In 2 of the 14 stables the egg reductions were close to the limit of 95%, 91 and 93%, respectively. In 1 stable the egg reductions indicated resistance to PYR as well as detection of resistance to FBZ, 94% reduction for PYR and 85% for FBZ. No signs of resistance were detected to IVM. The investigation was performed in late autumn and winter, and due to the climatic conditions and cleaning procedures in the stables no reinfection took place during this period. The faecal egg count reduction from treatment till day 90 post treatment was used as an expression of the effect of PYR and IVM on the early stage (hypobiotic), late third stage and fourth stage larvae in the gut wall. This was justified because there was no reinfection and because the 14 day post treatment egg counts were zero or close to zero for the PYR and IVM treatment groups. The effects of PYR and IVM on the larval stages were compared and no statistically significant differences were found.